INTEGRASI NILAI-NILAI MORAL BUDDHIS DALAM MATERI PEMBELAJARAN BAHASA INGGRIS BAGI ANAK USIA DINI: STUDI DESKRIPTIF PADA KARYA MAHASISWA PAUD INSTITUT NALANDA - Gustiya Gandha Metri (Jurnal Citra Pendidikan, 2026)
Abstract (English) In the Education 5.0 era, English language teaching for Early Childhood Education (ECE) is required to focus not only on linguistic proficiency but also on the internalization of ethical values. This study aims to describe the integration patterns of Buddhist moral values within English learning materials developed by ECE students at the Nalanda Institute. Utilizing a descriptive qualitative approach, this research analyzes students' instructional works, including lesson plans (RPP), teaching modules, and learning media, as the primary data sources. Data collection was conducted through document analysis and semi-structured interviews, using the Miles, Huberman, and Saldana data analysis model. The results indicate that the integration of Buddhist moral values is implemented through three main strategies: vocabulary selection that transforms abstract Dharma concepts into applicable adjectives (such as "gentle" and "helping others"), the adaptation of story narratives based on Jataka fables with repetitive dialogue, and media visualization that combines spiritual symbols with modern aesthetics. The findings also reveal that the use of Project-Based Learning (PjBL) strategies and teacher support play a crucial role in reducing students' speaking anxiety while simultaneously strengthening their character. This study concludes that the students' works reflect a hybridization of global competence and local spirituality, proving that foreign language teaching can serve as an effective means to develop children's rational and moral potential holistically.